The donation of human biological material for brain organoid research: the problems of consciousness and consent - Kataoka, M; Gyngell, C; Savulescu, J; Sawai, T (Springer, 2024)
Human brain organoids are three-dimensional masses of tissues derived from human stem cells that partially recapitulate the characteristics of the human brain. They have promising applications in many fields, from basic research to applied medicine. However, ethical concerns have been raised regarding the use of human brain organoids. These concerns primarily relate to the possibility that brain organoids may become conscious in the future. This possibility is associated with uncertainties about whether and in what sense brain organoids could have consciousness and what the moral significance of that would be. These uncertainties raise further concerns regarding consent from stem cell donors who may not be sufficiently informed to provide valid consent to the use of their donated cells in human brain organoid research. Furthermore, the possibility of harm to the brain organoids raises question about the scope of the donor’s autonomy in consenting to research involving these entities. Donor consent does not establish the reasonableness of the risk and harms to the organoids, which ethical oversight must ensure by establishing some measures to mitigate them. To address these concerns, we provide three proposals for the consent procedure for human brain organoid research. First, it is vital to obtain project-specific consent rather than broad consent. Second, donors should be assured that appropriate measures will be taken to protect human brain organoids during research. Lastly, these assurances should be fulfilled through the implementation of precautionary measures. These proposals aim to enhance the ethical framework surrounding human brain organoid research.